2012
DOI: 10.1371/journal.pone.0029886
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RNA Polymerase Primary σ70 as a Therapeutic Strategy against Methicillin-Resistant Staphylococcus aureus by Antisense Peptide Nucleic Acid

Abstract: BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) causes threatening infection-related mortality worldwide. Currently, spread of multi-drug resistance (MDR) MRSA limits therapeutic options and requires new approaches to “druggable” target discovery, as well as development of novel MRSA-active antibiotics. RNA polymerase primary σ70 (encoded by gene rpoD) is a highly conserved prokaryotic factor essential for transcription initiation in exponentially growing cells of diverse S. aureus, implying poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…Therefore, highperformance delivery of LNA is mandatory. (KFF) 3 K conjugated with PNA or phosphorodiamidate morpholino oligomer dramatically increased cell permeability and uptake of antisense oligonucleotides in a series of bacteria, including S. aureus, E. coli, and Salmonella enterica (16,24,30). To date, few studies have been performed to improve the permeability of LNA into bacteria through conjugation with the peptide (KFF) 3 K. In the present study, we synthesized the conjugated PLNA with (KFF) 3 K and LNA using the Cys-SMCC-C6 linker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, highperformance delivery of LNA is mandatory. (KFF) 3 K conjugated with PNA or phosphorodiamidate morpholino oligomer dramatically increased cell permeability and uptake of antisense oligonucleotides in a series of bacteria, including S. aureus, E. coli, and Salmonella enterica (16,24,30). To date, few studies have been performed to improve the permeability of LNA into bacteria through conjugation with the peptide (KFF) 3 K. In the present study, we synthesized the conjugated PLNA with (KFF) 3 K and LNA using the Cys-SMCC-C6 linker.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have shown that the translation start codon region of mRNA is the effective region for antisense inhibition (13-15). Recently, some studies have demonstrated that antisense agents targeting non-start codon regions have efficient antisense effects, such as PNA targeting of rpoD mRNA of MRSA and LNA targeting of the IRES of hepatitis C virus (12,16). This implies that possible targeting sites are generally nucleotide sequences free of any double-stranded secondary structures, which can be theoretically forecasted by RNA structure software (17).…”
mentioning
confidence: 99%
“…The 2.2 -CH interaction involves ␤= residues R275, R278, R281, L282, I291, N294, and M298 and 70 residues Q403, Q406, E407, I410, and M413 (37,38,176,177), but this is a nontraditional drug target as it lacks any deep clefts, which are considered desirable binding sites for small molecules. Nevertheless, a peptide-based study showed that peptides mimicking 2.2 could inhibit RNAP-binding to prevent in vitro transcription initiation, and prevention of production by antisense peptide nucleic acids could inhibit the growth of clinically relevant multidrug-resistant S. aureus (178,179).…”
Section: The Rnap-interactionmentioning
confidence: 99%
“…Those patients whose tumors are found to overexpress bcl-2 might then be good candidates for treatments that include down-regulation of bcl-2, such as targeted immunotherapy, radioimmunotherapy, or antisense therapy. In preclinical settings, peptide nucleic acid (PNA) has been evaluated for antisense therapy against a wide range of diseases including bacterial and viral infections, lymphoma, Alzheimer's disease and allograft survival [9][10][11][12][13][14][15][16]. PNA is a DNA-like molecule with high stability, binding affinity and specificity to complementary mRNA targets [17].…”
Section: Introductionmentioning
confidence: 99%